Speculating on the Future of Digital Tools for Qualitative Research. (September 2016) - Davidson, Judith; Paulus, Trena; Jackson, Kristi
Development in digital tools in qualitative research over the past 20 years has been driven by the development of qualitative data analysis software (QDAS) and the Internet. This article highlights three critical issues for the future digital tools: (a) ethics and the challenges, (b) archiving of qualitative data, and (c) the preparation of qualitative researchers for an era of digital tools. Excited about the future and the possibilities of new mash-ups, we highlight the need for vibrant communities of practice where developers and researchers are supported in the creation and use of digital tools. We also emphasize the need to be able to mix and match across various digital barriers as we engage in research projects with diverse partners.